If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -3)(y + 10) = 0 Reorder the terms: (-3 + y)(y + 10) = 0 Reorder the terms: (-3 + y)(10 + y) = 0 Multiply (-3 + y) * (10 + y) (-3(10 + y) + y(10 + y)) = 0 ((10 * -3 + y * -3) + y(10 + y)) = 0 ((-30 + -3y) + y(10 + y)) = 0 (-30 + -3y + (10 * y + y * y)) = 0 (-30 + -3y + (10y + y2)) = 0 Combine like terms: -3y + 10y = 7y (-30 + 7y + y2) = 0 Solving -30 + 7y + y2 = 0 Solving for variable 'y'. Factor a trinomial. (-10 + -1y)(3 + -1y) = 0Subproblem 1
Set the factor '(-10 + -1y)' equal to zero and attempt to solve: Simplifying -10 + -1y = 0 Solving -10 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1y = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1y = 0 + 10 -1y = 0 + 10 Combine like terms: 0 + 10 = 10 -1y = 10 Divide each side by '-1'. y = -10 Simplifying y = -10Subproblem 2
Set the factor '(3 + -1y)' equal to zero and attempt to solve: Simplifying 3 + -1y = 0 Solving 3 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 0 + -3 -1y = 0 + -3 Combine like terms: 0 + -3 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3Solution
y = {-10, 3}
| 4-x/3x-12 | | Y=2.17+83x | | 99999999999999+y-987596526=56+925y | | 8m^2+18m+7=0 | | (x+5)(x-3)=15 | | 7p+4-2p+1=8p+2 | | 100=x+(x*4)+(x*4) | | (x+3)+(x+8)=21 | | 5^7x-9=1/125 | | ln(8x+1)=6 | | 92x=36 | | 6-3x-5x-x=10 | | 2ef+3ef= | | 5x+(7x+2)+(7x+6)= | | 2m^2=-4m+6m | | 7q-4q+8= | | 3b^4+18b^3+27b^2= | | log(2x-4)=-0.7 | | 2x+5=-2x-8-x | | -40=8(x-3)-3/2(6x-16 | | .16x+1500=x | | (X)2+(Y-1)2=81 | | 0=16t^2+96t-140 | | 5k^2+20k+100=0 | | 5k^2+20k+100=100 | | (x-5)-(x-12)= | | (t/2-20)/4=4 | | 5*7x^2y=175 | | 21/15=3x-2/5 | | 12/3x=36/63 | | 5m(4m+11)= | | Y=(8-x)^1/2 |